Desmoplasia in Pancreatic Cancer. Can We Fight It? - E. E. Merika; K. N. Syrigos; M. W. Saif (Gastroenterology Research and Practice)
The hallmark of pancreatic tumours, the desmoplastic reaction, provides a unique microenvironment that affects pancreatic tumour behaviour, its ability to grow and metastasize as well as resist the effects of chemotherapy. Complex molecular interactions and pathways give rise to the desmoplastic reaction. Breakdown or penetration of the desmoplastic reaction may hold the key to overcoming the limits of delivery of efficacious chemotherapy or the development of new targeted treatments. Herein we discuss such new developments to fight the desmoplastic reaction, including inhibitors of the epidermal growth factor, fibroblast growth factor, the hedgehog pathway, as well as new molecular targets like CD40 agonist and its effects on T cells, extracellular matrix modifying enzymes such as LOXL2 inhibitor and novel tumour penetrating peptides for delivery of drugs.